Furação em compósito de fibras do caule da bananeira e poliuretano derivado do óleo de mamona - Ellenberger, Alessandro (2022)
Natural fibers composites obtained from agricultural waste processes appear as an alternative to materials from non-renewable sources. The combination of banana fibers and polyurethane derived from castor oil originates a biodegradable composite, from renewable sources and with good physical-mechanical properties. Drilling of composites with natural fibers is challenging due to the non-homogeneous structure of the material and the behavior of the fibers and polymer matrix. This work investigated the drilling process in composites with banana stem fibers and polyurethane derived from castor oil developed from mechanized and manual processes, using different drill models and cutting parameters. The quality of the holes were evaluated, the forces involved in the machining were measured, the conditions of the drills after the process were observed, the types of chips generated and a post-processing was proposed. The results showed that the twist drill with a cutting speed of 19 m/min and a feed of 0.1 mm was the most suitable for drilling in the composite with mechanically process. For the composite with manually cut fibers, the three-point drill using a cutting speed of 38 m/min and a feed of 0.1 mm was the most suitable. The drill model with the movement of entry and exit in the material, the behavior of the banana fibers and feed rate showed to influence the generation of damages in the drilling of these composites.